Analisis Pengaruh Penerapan Akuntansi Pertanggungjawaban Terhadap Kinerja Manajer Pusat Laba di Warung Paskal Bandung - Se Tin -; Taufik Hidayat (Universitas Kristen Maranatha, 2012)
The purpose of the research is to improve the performance of managerstake the right decisions either in an order of goods, knowing the condition of thegoods, and stock of goods. Accounting is one of the concepts of managementaccounting and accounting systems are linked and tailored to the centers ofaccountability that exist within the organization. The term of this accounting willlead to the accounting process that reported up to how good the responsibilitycenter managers can manage the work directly under his control and which he isresponsible or a system that measures and action plans of each responsibilitycenter. In carrying out these studies the authors obtained information from field research (interviews and distributed questionnaires) after it is examined with the concepts that are based on theory (Research Library) thus obtained primary data and secondary data. After getting the data the authors make the scale of measurement and testing such as test validity, test reliability, and the authors analyze whether the accounting liability or no significant influence on the Paskal Stall, it can be input to public satisfaction Paskal so shoppers can keep maintained and even increased profits.